2022
DOI: 10.48550/arxiv.2202.13704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-resolved chiral X-Ray photoelectron spectroscopy with transiently enhanced atomic site-selectivity: a Free Electron Laser investigation of electronically excited fenchone enantiomers

Abstract: Chiral molecules are widespread in nature, playing a fundamental role in bio-chemical processes and in the origin of life itself. The observation of dynamics in chiral molecules is crucial for the understanding and control of the chiral activity of photo-excited states. One of the most promising techniques for the study of photo-excited chiral systems is time-resolved photoelectron circular dichroism (TR-PECD), which offers an intense and sensitive probe for vibronic and geometric molecular structure as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Experimental data confirmed that a soft X-ray FEL source is very effective in timeresolved PECD for studying dissociating chiral cations [34] and for time-resolved photoelectron spectroscopy (XPS) applied to site-specific analysis suitable to distinguish the contributions of different atoms of the same chemical element simultaneously probed [35]. Following these promising results, Faccialà et al investigated at the C K-edge the chirality of fenchone, a prototypical organic molecule, using both time-resolved XPS and PECD [36]. The experiment was carried out at the FERMI-FEL, currently the only facility that delivers high-temporal coherent and circular polarized pulses in this energy domain.…”
Section: -3 the Electronic Structure Of Photo-excited Chiral Moleculesmentioning
confidence: 88%
“…Experimental data confirmed that a soft X-ray FEL source is very effective in timeresolved PECD for studying dissociating chiral cations [34] and for time-resolved photoelectron spectroscopy (XPS) applied to site-specific analysis suitable to distinguish the contributions of different atoms of the same chemical element simultaneously probed [35]. Following these promising results, Faccialà et al investigated at the C K-edge the chirality of fenchone, a prototypical organic molecule, using both time-resolved XPS and PECD [36]. The experiment was carried out at the FERMI-FEL, currently the only facility that delivers high-temporal coherent and circular polarized pulses in this energy domain.…”
Section: -3 the Electronic Structure Of Photo-excited Chiral Moleculesmentioning
confidence: 88%
“…Experimental data confirmed that a soft X-ray FEL source is very effective in timeresolved PECD for studying dissociating chiral cations [34] and for time-resolved photoelectron spectroscopy (XPS) applied to site-specific analysis suitable for distinguishing between the contributions of different atoms of the same chemical element that are simultaneously probed [35]. Following these promising results, Faccialà et al investigated at the C K-edge the chirality of fenchone, a prototypical organic molecule, using both time-resolved XPS and PECD [36]. The experiment was carried out at the FERMI-FEL, currently the only facility that delivers high-temporal coherent and circular polarized pulses in this energy domain.…”
Section: The Electronic Structure Of Photo-excited Chiral Moleculesmentioning
confidence: 99%
“…For this reason, many synchrotron beamlines around the world are dedicated to static XUV circular dichroism experiments in atoms, molecules, and solids in their ground state [85,86,87,88,89]. One of the burgeoning goals in the community is to extend such XUV dichroism experiments to the ultrafast regime, where dynamical out-of-equilibrium properties of matter can be investigated [90,42,91,92,43,93]. The ultrashort duration of XUV pulses generated using high-order harmonic generation makes this approach very appealing for pushing this goal forward.…”
Section: All-reflective Xuv Quarter-wave Plate and Polarization Chara...mentioning
confidence: 99%